GE_GERICHTE C/20012/2017 vom 15. Januar 2019 - GE Cour de justice (2019)
RÉPUDIATION(DROIT SUCCESSORAL) ; DÉLAI ; MOTIVATION DE LA DEMANDE | CPC.321.al1; LP.193.al1.ch1; LP.193.al1.ch2; CC.566.al2; CC.567.al1; CC.567.al2